Mg-Al-MoO4 layered double hydroxides used as catalysts for the oxidation of styrene - Thao, Nguyen Tien; Trung, Nguyen Duc; Long, Dang Van; Thuc, Vu Dong (Vietnam Journal of Chemistry, 2017)
Mg-Al layered double hydroxides have been prepared by the precipitation method and characterized by the physical methods such as XRD, EDS, SEM. The synthesized solids showed the layered hydroxide structure with molybdate and carbonate anions as interlayer compensating anions in the uniform particles. While Mg-Al-CO3 is inactive for the liquid oxidation of styrene, Mg-Al-MoO4–LDH catalyst exhibits a good activity in the conversion of styrene into benzaldehyde and phenyl oxirane. The catalytic activity and product selectivity depend on the reaction conditions and oxidant nature. The styrene conversion is moderate about 10-15 % and the total selectivity to benzaldehyde and styrene oxide reached 99 % as air and t-butyl hydrogen peroxide used as milder oxidants. Keywords. Benzaldehyde, styrene, molybdate, hydrotalcite, oxidation.